Impact of juice processing of Costa Rican guava (Psidum friedrichsthalianum) on the physicochemical properties, total phenols and antioxidant capacity - Navarro Bolaños, Laura Patricia (2024)
Psidium plants are commonly consumed in processed forms, leading to a need to evaluate the impact of processing on bioactive compounds. The purpose of this study is to assess the effect of Costa Rican guava juice processing on physicochemical and antioxidant characteristics. Five samples corresponding to distinct phases in the juice processing were evaluated. Total polyphenols were measured using the Folin-Ciocalteu method, while antioxidant activity was assessed using various methodologies, including chemical methods (DPPH and ORAC) and cell assays with kidney cell cultures, liver homogenates, and erythrocytes. Results revealed variations in the impact of the juice processing stages on total polyphenols and for each antioxidant assay, evidencing that different polyphenols counteract in each technique. Significant decreases (ranging from 27 % to 58 %, p < 0.05) were primarily observed during the pressing stage, while thermal treatments resulted in nonsignificant reductions. This study demonstrated a decline in antioxidant activity during the processing of Costa Rican guava juice underscoring the need for continued efforts to optimize processing conditions and enhance the retention of health-promoting properties in the juice.